That Smart Dude: A Qualitative Investigation of the African American Male Scholar-Baller Identity. (June 2020) - Fuller, Rhema D.; Harrison, C. Keith; Bukstein, Scott J.; Martin, Brandon E.; Lawrence, S. Malia; Gadsby, Paige
The intersection of education, sport, and identity are important topics for urban education and educators. Using data collected from interviews with 27 African American male college athletes, the current study investigated the lived experiences of this demographic group as they formed ideas about "self" within the realm of higher education. Our findings revealed that their definition of masculinity was at the core of their identities. In addition, participants saw themselves as more than athletes—They were scholars and productive members of surrounding communities. Furthermore, interactions with women, teammates, and non-athletic peers influenced participants' self-perceptions. Theoretical and practical implications are discussed.